Estimates of some approximating characteristics of the classes of periodic functions of one and many variables
UDC 517.5 We obtain the exact-order estimates for some approximating characteristics of the classes W^r _p,α and B^r _p,θ of periodic functions of one and many variables in the norm of the space B_∞, 1., number=8, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Romanyuk, A. S. and Romanyuk, V. S., year=2019, month=Aug., pages=1102–1115